The Influence of the Type of Feed Medium on the Growth of Hermetia illucens larvae in the Process of Reducing Organic Waste S - Syaiful Bahri; Yuli Ambarwati; Ni Luh Gede Ratna Juliasih; Muhammad Trijatmiko (Stannum : Jurnal Sains dan Terapan Kimia, 2023)
Increasing the effectiveness of waste management and processing is by utilizing waste into a protein source of fish feed ingredients through the bioconversion process. One of the insects that is usually used as a bioconversion process is Hermetia illucens or better known as BSF (Black Soldier Flies). This study was conducted to look at the bioconversion process carried out by the larvae of Hermetia illucens and to look at the morphology of the length and body weight of the larvae of Hermetia illucens. This research was conducted at the Integrated Waste Treatment Plant (TPST) of Lampung University. The variety of waste used is market waste, tofu dregs, and a mixture of market waste and tofu dregs (1:1). The most optimal results of measuring the body length of Hermetia illucens larvae was tofu pulp feed type, which is an average of 2.17 cm. The most optimal results of measuring the body weight of Hermetia illucens larvae are Hermentia Illucens larvae of the market waste feed type with an average weight of 0.336 g. Proximate test results from Hermentia Illucens larvae are the larvae of tofu pulp feed media with a protein content of 41.27% and fat of 27.42%, it can be concluded that Hermentia Illucens larvae From the feed medium tofu pulp is best because it contains high protein content and not too high fat con